2017
DOI: 10.1111/1365-2656.12659
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of transmission and the dynamics of networks

Abstract: A toy example depicted here highlighting the results of a study in this issue of the Journal of Animal Ecology that investigates the impact of network dynamics on potential disease outbreaks. Infections (stars) that spread by contact only (left) reduce the predicted outbreak size compared to situations where individuals can become infected by moving through areas that previously contained infected individuals (right). This is potentially important in species where individuals, or in this case groups, have over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Modelling approaches provide one solution to this issue by incorporating the uncertainty associated with the codynamics of network structure and infection into static models, offering insight where the interplay is an empirical unknown (Silk et al., ). However, we have shown that disease can have a quantitative, nonlinear effect on the contact behaviour of social animals, indicating that using dynamic models explicitly incorporating this feedback between infection and behaviour will likely improve predictions (Farine, ). The relationship between β c and β p may also drive evolutionary change in both host and parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling approaches provide one solution to this issue by incorporating the uncertainty associated with the codynamics of network structure and infection into static models, offering insight where the interplay is an empirical unknown (Silk et al., ). However, we have shown that disease can have a quantitative, nonlinear effect on the contact behaviour of social animals, indicating that using dynamic models explicitly incorporating this feedback between infection and behaviour will likely improve predictions (Farine, ). The relationship between β c and β p may also drive evolutionary change in both host and parasite.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most useful applications of dynamic networks in epidemiology is the possibility to simulate and explore the transmission of pathogens on the basis of the different parameters that characterise them like, the probability of transmission, the first individual/s infected or transmission within a specific period of time [24]. In the dynamic network we simulated the transmission of a theoretical pathogen transmitted through both direct and indirect pathways, according to our spatio-temporal definition of direct and indirect interaction, to explore the potential role of wild species in the transmission to cattle.…”
Section: Simulation Of Pathogen Transmissionmentioning
confidence: 99%
“…Nevertheless, the temporal changes in the interactions structure inevitably affect the dynamic of infection [21,22], by changing the properties of the network, that result in speeding up or slowing down the transmission rates [23]. Thus, to better determine how an infection spreads, moving from a static network to a dynamic one is required [24].…”
Section: Introductionmentioning
confidence: 99%
“…This sickness-induced ‘social distancing’ can be important for modelling pathogen transmission as a social network changes over time (i.e. a dynamic social network [4]). Tracking the effects of sickness behaviour on a dynamic social network requires large datasets with temporal and spatial resolutions that are high enough to be ecologically useful.…”
Section: Introductionmentioning
confidence: 99%